Islam, Civil Society, dan Perubahan Politik di Era Transisi Demokrasi: Studi Peran Nahdlatul Ulama (NU) Jember dalam Membangun Relasi Kekuasaan dengan Negara di Tingkat Lokal: Islam, Civil Society, and Political Change in the Democratic Transition Era: A Study of the Role of Nahdlatul Ulama (NU) Jember in Building Power Relations with the State at the Local Level - M. Khusna Amal (Fenomena, 2011)
After The New Era (Soeharto’s regime), the position of our country is claimed to be less expressive than The New Era authoritarianism regime. Our country seems like a new political stage that is so open that every social element can reach it. This melting political system enables every social element to be involved in practical politics to gain access to the state's political stage. Nevertheless, NU Jember also responded to the changing political system after The New Era by engaging in politics. NU Jember's structural constraints in practical politics were addressed by involving the traditionalist Muslim organization in the practical political arena without transforming the organization into a political party, but using it as an asset to participate in practical politics. These politically pragmatic practices led NU Jember to be evaluated as less capable of playing a progressive role in promoting a rapid transition to regional democracy. Setelah Era Baru (rezim Soeharto), posisi negara kita dianggap kurang ekspresif dibandingkan dengan rezim otoritarian Era Baru. Negara kita seolah menjadi panggung politik baru yang sangat terbuka sehingga setiap elemen sosial dapat mencapainya. Sistem politik yang mulai mencair ini memungkinkan setiap elemen sosial terlibat dalam politik praktis untuk mendapatkan panggung politik negara. Namun demikian, NU Jember juga merespons perubahan sistem politik pasca-Era Baru dengan terlibat dalam politik. Kendala struktural NU Jember dalam politik praktis diselesaikan dengan melibatkan organisasi muslim tradisional dalam panggung politik praktis tanpa mengubah organisasi menjadi partai politik, tetapi menggunakan organisasi sebagai aset untuk terlibat dalam dunia politik praktis. Praktik politik yang dianggap berorientasi pragmatis ini membuat NU Jember dinilai kurang mampu memainkan peran progresif dalam mendorong transisi cepat menuju demokrasi regional.